Interaction of intratumoral microbiota with the tumor immune microenvironment and its impact on cancer progression - Tingting, Yan; Xiaoling, Zhu; Yu, Zhang; Yan, Luo; Yang, Luo; Xueqin, Shang; Shikai, Tang (Frontiers in Oncology, 2025)
The intratumoral microbiota, a critical component of the tumor microenvironment (TME), has been demonstrated to significantly impact tumor progression and therapeutic outcomes. Research indicates that intratumoral microbes can affect tumorigenesis, metastasis, and therapeutic response through various mechanisms, such as inducing DNA damage, activating oncogenic signaling pathways, and modulating immune responses. Furthermore, the microbiota exerts dual regulatory effects on the tumor immune microenvironment (TIME), either enhancing anti-tumor immunity or promoting immunosuppression, thereby presenting novel targets for cancer therapy. In this paper, we conduct a review of the origin and composition of the intratumoral microbiota and its dynamic interactions with the TME by synthesizing data from multiple cancer studies. This review elucidates the complex role of the microbiota within the TIME and explores its potential for clinical application.